2007
DOI: 10.1590/s1516-80342007000400009
|View full text |Cite
|
Sign up to set email alerts
|

Teste de padrão harmônico em escuta dicótica com dígitos - TDDH

Abstract: OBJETIVO: O presente estudo teve como objetivos a elaboração de um teste de processamento auditivo com estímulos de fala cantada em tarefa dicótica, a caracterização do desempenho de ouvintes neste teste; e a comparação deste desempenho com o observado no Teste Dicótico de Dígitos. MÉTODOS: Elaborou-se o teste com estímulos de fala cantada que foi denominado de Teste de Padrão Harmônico em Escuta Dicótica com Dígitos, composto de uma etapa de integração biaural e duas de separação biaural (direita/esquerda), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
4
0
4
Order By: Relevance
“…The alteration in temporal processing may be attributed to the fact that phonemes in Portuguese are easier to be distinguish than phonemes of other foreign languages such as English, that is, the auditory system needs to make less effort, which generates a discernment less accurate in frequency and length (21) . In relation to the dichotic listening, when there is correct processing of stimuli in the right ear, one can surmise proper functioning of the left hemisphere and, in turn, abnormal results in both ears suggest alterations in the left hemisphere for speech processing (22) . The dichotic listening task was also the most altered and prevailing one in relation to all complaints that were analyzed in the study, mainly in the individuals that reported having learning disability.…”
Section: Discussionmentioning
confidence: 99%
“…The alteration in temporal processing may be attributed to the fact that phonemes in Portuguese are easier to be distinguish than phonemes of other foreign languages such as English, that is, the auditory system needs to make less effort, which generates a discernment less accurate in frequency and length (21) . In relation to the dichotic listening, when there is correct processing of stimuli in the right ear, one can surmise proper functioning of the left hemisphere and, in turn, abnormal results in both ears suggest alterations in the left hemisphere for speech processing (22) . The dichotic listening task was also the most altered and prevailing one in relation to all complaints that were analyzed in the study, mainly in the individuals that reported having learning disability.…”
Section: Discussionmentioning
confidence: 99%
“…Então, por meio das situações dicóticas, oferecidas o tempo todo pelo ambiente, os indiví-duos conseguem diferenciar as complexidades acústicas dos sons como intensidade, frequência e fase 4 . Assim, para se processar a informação, via sentido da audição, os sons devem ser detectados e interpretados, ou seja, os estímulos acústicos são recebidos pelo sistema periférico e codificados neuralmente 5 . A modalidade auditiva divide-se em algumas submodalidades: discriminação da intensidade sonora, discriminação tonal, identificação de timbres, localização espacial dos sons, compreensão da fala e a interpretação de sons complexos 3 , como, por exemplo, a música.…”
Section: Métodounclassified
“…Qualquer perda ou atraso que aconteça em algumas das etapas do PA origina o que se denomina DPA. O objetivo da avaliação de PA é determinar a presença ou ausência do distúrbio, descrever a extensão do mesmo, avaliar os efeitos da maturação do SNAC, detectar o 'local' da disfunção auditiva, definir as habilidades preferenciais para a aprendizagem, estabelecer a reabilitação e avaliar os benefícios de tratamento ou encaminhamento a outros profissionais 6,7 . A avaliação comportamental da função auditiva central é composta de testes especiais que observam o comportamento auditivo, como testes dicóticos, testes de processamento temporal, testes monoaurais de baixa redundância e testes binaurais 8 .…”
Section: Apresentação Dos Casosunclassified